Cardio-Oncology: A New Discipline in Medicine and Its Relevance to Hematology - Spannbauer, Andreas; Bergler-Klein, Jutta (Hämostaseologie, 2024)
Cardio-oncology, a burgeoning subspecialty, addresses the complex interplay between cardiology and oncology, particularly in light of increased cardiovascular (CV) disease mortality in cancer patients. This review provides a comprehensive overview of cardio-oncology with a focus on the therapies used in hematological malignancies. We explore the bidirectional relationship between heart failure and cancer, emphasizing the need for collaborative care. The review discusses risk stratification, highlighting the importance of baseline CV risk assessment and personalized surveillance regimens. Primary and secondary prevention strategies, including pharmacological interventions, are outlined. The review also delves into the cardiotoxicity associated with hematological cancer therapies, focusing on anthracyclines, Bruton kinase inhibitors, BCR-ABL tyrosine kinase inhibitors, CAR-T cell therapy, immune checkpoint inhibitors, multiple myeloma treatments, and hematopoietic stem cell transplantation. We then highlight the high risk of venous and arterial thromboembolisms in cancer patients and the challenges of anticoagulation management in cardio-oncology. Finally, the review touches on the importance of long-term follow-up and appropriate screening in cancer survivors at high risk of CV morbidity and mortality, based on their CV risk profile and the type and dose of cardiotoxic therapies they received such as anthracyclines or high radiation doses.
Keywords: cardio-oncology; cardiotoxicity; thrombosis; prevention